Comparison The Use Transparent Dressing With Conventional Fixation on Phlebitis Rates In Rumkitban 05.08.03 Sidoarjo - Aziz, Abdul (Kirana Publisher (KNPub), 2022)
Phlebitis is a major problem faced throughout the world and this incidence continues to increase. Phlebitis that occurs mechanically occurs when the type of fixation of the sterile gauze plaster is not strong enough or is not sticky enough, causing a change in the position of the catheter or friction in the internal area of the blood vessel which results in inflammation. Efforts to prevent the occurrence of phlebitis can be done by using a transparent dressing which can minimize bacteria entering through the attached vein, thereby reducing the occurrence of phlebitis. The aim of this research is to analyze the comparison of the use of Transparent Dressing with gauze on Phlebitis rates in RUMKITBAN 05.08.03 Sidoarjo. The design of this study is a comparative study, knowing the use of transparent dressings with conventional dressings. The number of samples taken using consecutive sampling was 73 patients. data collection method using an observation sheet instrument, the independent variables are Transparent dressing and conventional fixation, while the dependent variable is Phlebitis. In this study, researchers used SPSS software to carry out the Chi square test for research data analysis. Based on the results of the research and data analysis that has been carried out, it can be It was concluded that the results of research conducted on 73 respondents showed that there was a difference or influence between the use of Transparent Dressing and conventional dressing on Phlebitis rates at RUMKITBAN 05.08.03 Sidoarjo. From the research results, the author believes that the use of transparent dressings can prevent the entry of microorganisms that will enter intravenously because transparent dressings have no circulation at all.